2005
DOI: 10.1159/000089624
|View full text |Cite
|
Sign up to set email alerts
|

Reticulons as Markers of Neurological Diseases: Focus on Amyotrophic Lateral Sclerosis

Abstract: Reticulons (RTNs) are a family of proteins that are primarily associated with the endoplasmic reticulum. In mammals, four genes have been identified and referred as to rtn1, 2, 3 and the neurite outgrowth inhibitor rtn4/nogo. These genes generate multiple isoforms that contain a common C-terminal reticulon homology domain of 150–200 amino-acid residues. The N-terminal regions of RTNs are highly variable, and result from alternative splicing or differential promoter usage. Although widely distributed, the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 142 publications
2
10
0
Order By: Relevance
“…In keeping with this hypothesis, altered expression levels of reticulons have been observed in several neurological disorders (Fig. 2) [23,24]. For instance, RTN3 expression is increased in cerebral tissue obtained from Alzheimer disease patients [25].…”
Section: Reticulons In Membrane Traffickingsupporting
confidence: 56%
“…In keeping with this hypothesis, altered expression levels of reticulons have been observed in several neurological disorders (Fig. 2) [23,24]. For instance, RTN3 expression is increased in cerebral tissue obtained from Alzheimer disease patients [25].…”
Section: Reticulons In Membrane Traffickingsupporting
confidence: 56%
“…While their biological functions remain poorly understood, diverse biochemical and functional studies suggest various potential roles of these proteins, including the shaping of the tubular ER, regulated trafficking of vesicle proteins, neurite growth and exocytosis (GrandPre et al, 2000;Kiseleva et al, 2007;Steiner et al, 2004;Chen et al, 2000;Voeltz et al, 2006;Hu et al, 2007). Altered expression levels of RTNs are found in a variety of disease states, including neurological disorders (Yan et al, 2006;Fergani et al, 2005;Bandtlow et al, 2004). We and others have demonstrated that RTNs interact with BACE1 and negatively modulate BACE1 protease activity (He et al, 2004;He et al, 2006;Murayama et al, 2006;Wojcik et al, 2007;Kume et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…More than 18 murine ALS models have contributed not only to a better understanding of the disease but also to the search of potential therapeutic strategies. Nogo, also known as Neurite outgrowth inhibitor or Reticulon-4, was one of the first potential biomarkers suggested in early asymptomatic transgenic SOD1 G86R mice [36, 37]. Nogo is a member of the myelin-associated proteins, which possess axonal growth inhibitory activity.…”
Section: Potential Als Biomarkers Corresponding To Disease Progresmentioning
confidence: 99%